Comparison of five methods of cytomegalovirus antibody screening of blood donors. - Phipps, P H (1983)
A group of 120 sera from blood donors was screened by complement fixation and commercially available immunofluorescence, solid-phase fluorescence immunoassay, enzyme-linked immunosorbent assay, and indirect hemagglutination tests. Twenty-four of the sera were positive by three or more of the five tests and judged to be true positives; 89 were negative by three or more of the tests and considered to be true negatives. The tests were ranked for accuracy, sensitivity, specificity, false-positive rate, and false-negative rate. The indirect hemagglutination test scored best, followed by enzyme-linked immunosorbent assay, solid-phase fluorescence immunoassay, complement fixation, and immunofluorescence, in that order. When the tests were ranked on the basis of technical demands, turnaround time, requirement for special equipment, and subjectivity in reading, the indirect hemagglutination test again scored best, followed by solid-phase fluorescence immunoassay, enzyme-linked immunosorbent assay, immunofluorescence, and complement fixation in that order. Our findings suggest that the indirect hemagglutination test is the most reliable and effective commercially available test for the identification of those donors who are very unlikely to transmit cytomegalovirus to recipients.